Using Fairy Tales to Improve Narrative Writing Skills among EFL Students - Sam Hermansyah (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2025)
This study investigates the effectiveness of using fairy tales as instructional media to improve narrative writing skills among EFL students. The research employed a quasi-experimental design involving an experimental group and a control group. The participants were 48 second-year students of an Islamic junior high school in Indonesia, who were selected using a census technique. The experimental group received narrative writing instruction through fairy tales, while the control group was taught using conventional teaching methods. Data were collected through pre-test and post-test writing assessments and analyzed using descriptive and inferential statistics. The results revealed a significant improvement in the narrative writing performance of students taught using fairy tales. The post-test mean score of the experimental group was significantly higher than that of the control group. Statistical analysis using a t-test indicated that the difference between the two groups was statistically significant at the 0.05 level. These findings demonstrate that fairy tales are an effective instructional medium for enhancing EFL students’ narrative writing skills. Therefore, incorporating fairy tales into writing instruction is recommended to promote students’ engagement and improve their writing achievement.